Nivel de conocimiento del profesional de enfermería en la aplicación de la normativa ESAMyN, en el Hospital IESS Babahoyo, periodo junio-septiembre 2024. - Ochoa Vega, Leidy Tamara (2024)
The adoption of regulations and standards in the field of nursing is essential to ensure quality and safety in patient care. In this framework, the Regulations for Nursing Specialties and Areas of Care (ESAMyN) are established as a regulatory pillar in hospitals such as IESS Babahoyo. This regulation defines specific guidelines for nursing practice, including clinical protocols and standard operating procedures. However, the knowledge and application of the ESAMyN regulations by the nurses of the IESS Babahoyo Hospital need evaluation and analysis. This study aims to analyze the understanding and use of these guidelines by nurses in their daily practice to identify areas for improvement and strengthen the implementation of regulations that optimize health care. Aim: To identify the level of knowledge of the nursing professional in the application of the ESAMyN regulations, at the IESS Babahoyo Hospital, period June - September 2024. Methodology: The research was quantitative, descriptive, and field.